Learning style preferences of form five ESL students in Sarawak / Loretta George Winkle Engkasan - Winkle Engkasan, Loretta George (2013)
The purpose of this study was to investigate the preferred learning styles of 120 Form 5 ESL students from English Language Centre (ELC) and SMK Muara Tuang (GS) as well as to investigate the relationship of learning style preference to students’ proficiency level and to determine if there is a difference between students’ preferred learning style to students’ gender. A learning style refers to the ways of learning that include how learners perceive, interact with the respond to the learning environment. This study applied Reid’s (1995) taxonomy of six learning style preferences: visual, auditory, kinesthetic, tactile, group, and individual. This study employed a mixed-method approach. Quantitative and qualitative. Quantitatively, data was gathered from a sample of 120 Form5 students. Students were selected randomly according to their proficiency levels and gender. The students’ learning styles were elicited using the Perceptual Learning Styles Preference Questionnaire (PLSPQ) developed by Joy Reid. Qualitatively, individual interviews were conducted with 9 students from English Language Centre and 9 students from SMK Muara Tuang. The interviews were used to traingulate students’ choice of learning style preference. The study findings revealed respondents from both schools preferred the group learning style the most followed by kinesthetic learning style. The study found that there was significant difference in students’ learning style preference and their proficiency level in ELC. The study also found that there was a relationship between students’ learning styles and gender in ELC. The study concluded with the importance of understanding students’ learning style preference. The study suggested the measures instructors should take into the consideration with regards to students’ language learning style preference as well as academic performance and gender in order to obtain the a learning environment that would promote optimal learning and meeting students’ expectations and needs in the classroom.